The use of analgesics and anti-inflammatories in an oral surgery service in Medellín, Colombia, 2013-2015 - Hernández-Viana, Stefanía; Silva-Gómez, Natalia; Galvis-Pareja, David Andrés; Martínez-Pabón, María Cecilia (Revista Facultad de Odontología Universidad de Antioquia, 2019)
Introduction: dental surgical procedures trigger an inflammatory response, for which dental practitioners prescribe analgesic and anti-inflammatory medications using pharmacological guidelines that require knowledge on the use of medicines in a given environment. The aim of the present study was to identify the analgesics and anti-inflammatory drugs most commonly prescribed at the oral surgery service of the Universidad de Antioquia School of Dentistry. Methods: this retrospective descriptive study reviewed the clinical records of the oral surgery service in the period January 2013-August 2015. A total of 1,177 records were reviewed, and 709 were selected for analysis. Results: 53.1% of the drugs prescribed were non-selective Nonsteroidal Anti-Inflammatory Drugs (NSAIDs). Ibuprofen was formulated in 26.7% of all cases, followed by nimesulide with 24.1% and the combination of acetaminophen plus meloxicam with 10.2%. This same prescription pattern was observed in patients reporting no additional relevant medical history. In the case of gastric history, nimesulide was the drug of choice. 84% of all procedures were surgical extractions of third molars, with ibuprofen 600 mg postoperative for three days as the main therapeutic scheme. Conclusion: ibuprofen, nimesulide, and the combination acetaminophen plus meloxicam were the main analgesics and anti-inflammatory drugs prescribed in this study, according to medical and surgical records.